Environmental restoration of urban rivers in the metropolitan region of Rio de Janeiro, Brazil - S. A. Costa, Lucia; Vescina, Laura; Barcellos Pinheiro Machado, Denise (Environnement Urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2010)
This paper aims to expand our understanding of environmental discourses and practices in Brazil pertaining to urban water restoration, by focusing on the interrelations between environmental structure and urban occupation. For this purpose, it examines river and stream environmental restoration proposals within the Iguaçu Project located in Baixada Fluminense, in the state of Rio de Janeiro. The discussion begins with a brief description of the environmental restoration and landscape experience, followed by an exploration of the Baixada Fluminense social and environmental contexts. A program launched by the government is analyzed, emphasizing the development of riverside parks. The paper concludes by arguing that environmental restoration must be culturally specific in order to improve its efficacy.